2016
DOI: 10.3233/jad-150650
|View full text |Cite
|
Sign up to set email alerts
|

Diminished CRE-Induced Plasticity is Linked to Memory Deficits in Familial Alzheimer’s Disease Mice

Abstract: The mechanism underlying impaired learning and memory in Alzheimer's disease is not fully elucidated. The phosphorylation of cyclic-AMP response element binding protein (pCREB) in the hippocampus is thought to be a critical initiating step in the formation of long-term memories. Here, we tested CRE-driven gene expression following learning in mice harboring the familial Alzheimer's disease-linked APPswe/PS1ΔE9 mutations using CRE-β galactosidase reporter. We show that young adult APPswe/PS1ΔE9 mice exhibit imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 60 publications
3
40
0
Order By: Relevance
“…The role of CREB in AD pathology has been highlighted by the observation that pCREB is decreased in the nuclear fraction of postmortem prefrontal cortex (PFC) of individuals with AD, as compared to age‐matched, cognitively normal controls (Bartolotti et al ., 2016a,b). In the same study, the authors reported that pCREB expression in peripheral blood mononuclear cells paralleled pCREB expression in the PFC, proposing pCREB as a biomarker for cognitive function in AD.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The role of CREB in AD pathology has been highlighted by the observation that pCREB is decreased in the nuclear fraction of postmortem prefrontal cortex (PFC) of individuals with AD, as compared to age‐matched, cognitively normal controls (Bartolotti et al ., 2016a,b). In the same study, the authors reported that pCREB expression in peripheral blood mononuclear cells paralleled pCREB expression in the PFC, proposing pCREB as a biomarker for cognitive function in AD.…”
Section: Discussionmentioning
confidence: 99%
“…Whether or not Aβ monomers can oppose to this process, by sustaining IGF‐1 signaling, remains to be determined. Present data suggest that, at least, monomers and oligomers exert distinct effects on CREB protein functions, and that a loss of functional monomers and a building‐up of toxic oligomers could operate coordinately in determining the CREB dysregulation observed in AD (Pugazhenthi et al ., 2011; Bartolotti et al ., 2016a,b). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CREB is activated by phosphorylation and drives the expression of different target genes based on the brain region where it is activated 115. It is interesting to note that CREB is also emerging as an important molecule in AD research 116,117. Postmortem studies on AD brain tissue have reported down-regulation of CREB in the hippocampus 118.…”
Section: A Common Molecular Target In Ad and Depressionmentioning
confidence: 99%
“…Loss of CREB dependent gene expression after extrasynaptic NMDAR activation is a major event preceding cell death and neurodegeneration (2,(17)(18)(19)(20). Especially in AD, dysregulation of CREB dependent gene expression apparently plays a role in the onset of the disease and early synaptic dysfunction (18,19,(21)(22)(23)(24)(25)(26). The underlying mechanisms, as well as their relevance or contribution to Aβ-mediated CREB shut-off and neurodegeneration in AD, are still unknown (18,19).…”
Section: Introductionmentioning
confidence: 99%